Inovasi Makanan Tambahan Pada Bayi dan Anak (PMBA) dengan Bahan Lokal - Evy Ernawati; Siti Fadhilah; Fatimah sari; Febry HP; Fatya Nurul Hanifa; Yunri Merida (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
The growth and development of toddlers is something that needs great attention. This is because toddlerhood is a period of very rapid and critical growth, usually known as the golden age. There is potential for growth and development disorders in infants and toddlers due to a lack of balanced nutritional intake and knowledge about growth and development stimulation. PMT is one strategy for overcoming nutritional problems. Posyandu cadres as part of the posyandu driving team have a very important role in conveying the right information to mothers about PMT. Appropriate PMT can influence the nutritional status of toddlers. The aim of this community service activity is to increase the knowledge of posyandu cadres regarding proper feeding of babies and children with local ingredients. The methods used include education and practice in making baby and children's food using local ingredients. The results obtained by the cadres were an increase in knowledge after being given counseling which was shown by an increase in post test scores. The next activity is the practice of making baby and child food such as moringa nuggets, moringa vegetables, moringa pudding, dragon fruit pudding and so on. It is hoped that similar activities can continue to be carried out on an ongoing basis so that knowledge about feeding babies and children can be well disseminated to the community.